Preferred Leader Behaviour in the Business Sector of Lithuania: Follower Diversity Perspective - Minelgaitė, Inga; Littrell, Romie F.; Škudienė, Vida (Organizations and Markets in Emerging Economies, 2018)
Leadership roles in sustaining effective management have recently become paramount due to the need to keep up with the fast technical and societal developments. Moreover, business sectors in the postcommunist transformation settings are facing distinct leadership challenges suggesting a different pattern of leadership behaviour. The main contribution of this study was to build on follower-centric approach in leadership and investigate followers’ diversity in regard to leader behaviour preferences as a means to benchmark followers’ attitudes in the post-communist country still undergoing societal cultural shift. The purpose of the study was to investigate the leadership behaviours in Lithuanian cultural context. This study used 129 responses to the Leader Behaviour Description Questionnaire XII in order to identify the followers’ preferences of the leadership behaviour. ANOVA and correlation analyses were used to identify how followers’ age, level of education, and gender are related to leadership behaviour. The results indicated significant differences in regard to gender and education level of the follower towards the desired leader behaviour. However, the age of the follower did not affect leader behaviour preferences. This indicates that followers in Lithuania have diverse attitudes towards perception of effective leadership. Studying leader behaviour within the context of the followers’ socio-demographic characteristics contributes to the increase of knowledge about leadership behaviour in post-communist emerging economies.